Manufacturability of AlSi10Mg overhang structures fabricated by laser powder bed fusion. (15th December 2018) - Han, Quanquan; Gu, Heng; Soe, Shwe; Setchi, Rossi; Lacan, Franck; Hill, Jacob
Abstract: The main advantage of laser powder bed fusion (LPBF) is its use for directly manufacturing metal components with highly complex geometries. But the LPBF manufacture of overhang structures, also known as downward-facing surfaces, is a challenge because of the possibility of incurring distortion and dross defects. This paper presents a systematic examination of the manufacturability and structural integrity of AlSi10Mg overhang structures fabricated by LPBF using computational and experimental techniques. The experimental and simulation results indicate that the use of support structures facilitates the manufacturability and structural integrity of both full-circle and half-circle overhang structures. The influence of supports on circularity was found to be more beneficial as the diameter increased above 15 mm. The experiments also suggest that the use of supports plays a significant role in maintaining mechanical performance by successful fabrication of downward-facing surfaces free of dross defects. From a design perspective, small overhang features are preferable to large overhangs, especially when support removal is impractical. This study significantly contributes to design for metal additive manufacturing by providing an improved understanding of the manufacturability of overhang structures in applications intended for lightweight structural performance. Graphical abstract: Highlights: Fine base support enables distortion-free AlSi10Mg overhang structures manufactured by laser powder bed fusion. Part support needed to manufacture dross defect-free overhang structures when the nominal diameter is greater than 15 mm. Molten pools at dross zone found to be larger than that at the dross-free zone. Part support found to play a significant role in enhancing the compressive behaviour of full-circle overhang structures.